Study on the spawning habitat suitability of four major Chinese carps in the fluctuating backwater area of the Three Gorges Reservoir. (October 2022) - Xiao, Yi; Deng, Jinghong; Yang, Shengfa; Hu, Jiang; Wang, Li; Li, Wenjie
Highlights: The hydrodynamic conditions have altered significantly in the TGR after the TGD construction. A habitat suitability model was developed to evaluate the possibility of FMCC spawning in the TGR. The TGD operation brought temporal changes in the available WUA for FMCC in the TGR. The spawning period of FMCC was delayed from April to May after the TGD operation; The spawning sites of the FMCC decreased rapidly after the TGD operation. Abstract: The upstream of the Yangtze River has abundant fish resources and is home to the four major Chinese carps (FMCCs), which are economically important fish in the Yangtze River that reside in the fluctuating backwater area (FBA) of the Three Gorges Reservoir (TGR). Their spawning habitat has been influenced by the Three Gorges Dam (TGD) operations. This study investigated the effects of dam operation on spawning habitat suitability and the potential spawning sites of FMCCs, using a physical habitat suitability model combined with a two-dimensional (2D) hydrodynamic numerical model. The habitat model was verified by field measurements of the fish egg density in the FBA, illustrating the capability of predicting the spawning availability of FMCC by comparing the habitat suitability index (HSI) distribution and the weighted usable area (WUA) with the simulation scenarios before and after the TGD construction. The habitat model was then applied to evaluate the effects of TGD operation on spawning habitat suitability and potential spawning grounds in the FBA. These results implied that the TGD operation had negative effects on spawning habitat suitability and produced temporal changes in the available WUA in the FBA. The predictions revealed that impoundment of the TGD decreased the suitability of the hydrodynamic factors. The main spawning period was delayed from April to May, and the variation in the water level induced by the reservoir operation scheme was likely the main factor. The HSI distribution in the FBA showed that the potential spawning grounds decreased to one site located in the Mudong-Luoqi River section. Furthermore, there was a rapid reduction in WUAs, accounting for approximately 18% of that seen in 2001 (before the TGD operation). The results of this study can aid in the management of the spawning grounds of FMCCs in the TGR and provide efficient methods for improving spawning habitat suitability, such as adjusting the pool level of the TGD during the falling stage.